Maximization of production in knit dyeing industries - Islam, Md. Monowarul; Haque, A. F. M. Anwarul; Karim, A.N. Mustafizul (Department of Industrial and Production Engineering, BUET, 2002)
Dye house is the wet processing unit in a Knit dyeing industry. There are mainly three types of fabric processed in dye-house (i.e - White fabric, Color/Dyed fabric and P.C fabric). It is very important for dye-house to maintain an optimum ratio of these three products. Consequence of non-optimal proportion of these three products {or product mix) will result in improper production planning . leading to a loss in through output. Non-optimal product mix may lead to increase one type of product. This increased production of a particular type of fabric can overload the finishing area causing shortage of trolley for unloading the dyeing machines. As a result delivery is delayed from scheduled date leading to delay in shipment Moreover, in order to meet the deadline sometimes the company has to send the container by air instead of sea, resulting in significant loss. This paper addresses those problems and shows how to overcome those problems by adopting linear programming approach. A comparison in terms of production volume current planning approach and linear programming method is given.